Evolução estrutural de ligas Fe-Si processadas através de moagem de alta energia - Simões, Thiago Araújo (2011)
This work presents a study about microstructural evolution of nanocrystalline alloys Fe50%Si processed by milling of high energy. With the objective of pondering the process variables, a factorial design 2² with central point was used. The design formed the basis for the development of a semi-empirical model of Fe-Si phase formation, which subsequently led to the response surface equation. The samples were characterized by Xray Fluorescence, Scanning Electron Microscope (SEM), Mössbauer Spectroscopy and Xray diffraction. The structural changes are discussed based on obtained diffractograms and using the Rietveld refinement in the TOPAS software. By calculating the effects of variables, it's shown that for the characteristics of the used system, the milling time has a preponderant effect on the other ones. The study on the evolution of the performed lattice parameter shows the occurrence of two distinct phases with increasing rotation speed and milling time. This evolution demonstrates a transition from disordered to ordered phase of Fe-Si intermetallic compound.